2013
DOI: 10.1371/journal.pone.0063470
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoid Aggregates That Resemble Tertiary Lymphoid Organs Define a Specific Pathological Subset in Metal-on-Metal Hip Replacements

Abstract: Aseptic lymphocyte-dominated vasculitis-associated lesion (ALVAL) has been used to describe the histological lesion associated with metal-on-metal (M-M) bearings. We tested the hypothesis that the lymphoid aggregates, associated with ALVAL lesions resemble tertiary lymphoid organs (TLOs). Histopathological changes were examined in the periprosthetic tissue of 62 M-M hip replacements requiring revision surgery, with particular emphasis on the characteristics and pattern of the lymphocytic infiltrate. Immunofluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 50 publications
(84 reference statements)
5
56
0
3
Order By: Relevance
“…Interestingly, results of the present study also showed overall lower percentages of memory B cells in patients with a failed MoM hip implant with a pseudotumor than in patients with a well-functioning implant without a pseudotumor. These results may reflect the sequestration of memory B cells, possibly in secondary lymphoid organs or in periprosthetic tissues where lymphoid aggregates resembling tertiary lymphoid organs have been described in some patients with a MoM hip implant [29]. Interestingly, plasma cells have been found in periprosthetic tissues from failed MoM hip implants with a hypersensitivity reaction [38] and more specifically with a pseudotumor [32].…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, results of the present study also showed overall lower percentages of memory B cells in patients with a failed MoM hip implant with a pseudotumor than in patients with a well-functioning implant without a pseudotumor. These results may reflect the sequestration of memory B cells, possibly in secondary lymphoid organs or in periprosthetic tissues where lymphoid aggregates resembling tertiary lymphoid organs have been described in some patients with a MoM hip implant [29]. Interestingly, plasma cells have been found in periprosthetic tissues from failed MoM hip implants with a hypersensitivity reaction [38] and more specifically with a pseudotumor [32].…”
Section: Discussionmentioning
confidence: 94%
“…A total of 34 publications fit our inclusion criteria (Appendix 1). [7,8,14], and others [19,26,27,29,34,40] have illustrated histologic features suggestive of an immune reaction in tissues around some failed metal-on-metal hip implants (see subsequently). These features are characteristic, but a failed metal-on-PE implant may demonstrate similar histologic findings [17,41].…”
Section: Methodsmentioning
confidence: 95%
“…First, by confining our review to studies that included quantitative or semiquantitative grading of the histologic findings, we excluded many publications that have used only qualitative descriptions of periarticular findings [5,12,29,35,42,44,46] or that have focused on particle quantitation [13,30,45], cytokine detection [9,21], or lymphocyte subsets [29]. Among the studies that have graded morphologic features of periprosthetic tissues, many have not included conventional metal-on-PE or ceramic-on-polyethylene cases as controls, and differences in grading criteria among studies preclude pooling the data into larger groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations